BURSA EFEK DALAM EKONOMI ISLAM - Syahrul, H (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2013)
In the discussion of Islamic thought to reconstruct the conventional financial instruments that are not allowed by Sharai , and circulated in the capital markets , then submit proposals for the Muslim jurist and scientists on the alternative financial instruments in accordance with the new Islamic fiqh . The discussion outlined as follows: 1) The transfer of activities that firms issuing common stock and indulge in the forbidden activity toward longer lawful good , 2) Elimination of the terms relating to the preferred shares as collateral for the return of property and collateral for part of particular benefit to conform with the provisions of law , 3 ) Elimination of bonds that have a fixed interest rate and certain investments and turn them into securities that participate in the profits and losses without any guarantee on its back above the price or profit , 4) the jurist and Muslim scientists have ijtihad in Islamic economics in creating some new securities in accordance with the provisions of Mam . Among them are: Bond mudarabah letter al-muthlaqah al-Islamiya, al-mudaraba Letters Muqayyadah bi masyru muayyan , Surat al - mudaraba Muqayyadah bi blunt muayyan , Obiigasi mudaraba which can be converted into shares , Letter of special financing , special investment letter , letters of different deliberation , investment bonds Island.